2008
DOI: 10.1002/hed.20920
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma: The Princess Margaret Hospital experience

Abstract: Dulguerov classification best correlates with the patient's outcome. A combined approach is the preferred treatment. It makes no difference whether radiotherapy is given pre or postsurgical resection. Recurrence can occur even 15 years after treatment. Therefore, long-term follow-up is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 28 publications
(44 reference statements)
3
87
2
10
Order By: Relevance
“…The most frequent clinical manifestations are nasal obstruction (70%), epistaxis (46%), rhinorrhea, and headache. Anosmia, otalgia, and ocular pain are often present due to the neoplasm's invasion to adjacent structures [2,3,11,12] . During its growth, it extends to the skull base and can spread to the brain or spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent clinical manifestations are nasal obstruction (70%), epistaxis (46%), rhinorrhea, and headache. Anosmia, otalgia, and ocular pain are often present due to the neoplasm's invasion to adjacent structures [2,3,11,12] . During its growth, it extends to the skull base and can spread to the brain or spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…En la siguiente tabla se incluyen los datos de algunas de las series más recientes 2,16,17,37,41,42,48,60 (tabla 6):…”
Section: Revisión Bibliográficaunclassified
“…Sólo en unos pocos estudios se pudo considerar la supervivencia a los 10 años que fue del 52%. Revisando artículos con un número de casos superior a 25 incluyendo estudios más recientes, el rango de supervivencia a los 5 años sería del 55 al 89% y un periodo libre de enfermedad a los 5 años del 36,5 al 76% 2,[16][17]37,41,60 .…”
unclassified
“…There is no true standard of care for treatment, because no controlled trials have demonstrated superior outcomes. However, multimodality therapy is generally recommended for all but the smallest of tumors [15,16]. Surgery remains the mainstay of treatment for this malignancy.…”
Section: Surgical Approach To Skull-base Tumorsmentioning
confidence: 99%